Evaluation of dimensional stability of Iralgin and Alginoplast alginates after disinfection by sodium hypochlorite (5.2%) with immersion and spraying methods - Vojdani M; Derafshi R (Tehran University of Medical Sciences, 2006)
Background and Aim: Infection control is an integral part of dentistry and dental impressions are considered an important issue in cross contamination. The aim of this study was to investigate the dimensional stability of two irreversible hydrocolloid materials, Alginoplast and Iralgin after disinfection with 5.2% sodium hypochlorite, used with immersion and spraying methods. Material and Methods: In this experimental study, impressions were made of a master mandibular arch (Typodont) containing three stainless steel inserts on the occlucal surface of both mandibular first molars and in the lingual surface of the mandibular central incisors, which served as reference marks for making measurements. Two types of irreversible hydrocolloid (Iralgin and Alginoplast) were tested. 5.2% sodium hypochlorite was used in two methods of spraying and immersion to disinfect the samples. The control group was not disinfected. Casts were made of type III gypsum. Stone casts were measured with a Nikon profile projector.Kruskall-Wallis and Mann-Witney test were used for statistical analysis using p<0.05 as the limit of significance. Results: Casts prepared from Alginoplast disinfected by spraying method, were 0.38 % larger in anteroposterior and 0.06% smaller in cross arch dimensions, whereas those prepared from Alginoplast immersed in hypochlorite were 0.47% larger in anteroposterior and 0.11% smaller in cross arch dimensions. Casts made from Iralgin were smaller after both methods of disinfecting, (0.01% smaller in anteroposterior and 0.001% smaller in cross-arch dimensions after spraying and 0.04% smaller in anteroposterior and 0.03% smaller in cross-arch dimensions after immersing in sodium hypochlorite). Conclusion: Alginoplast and Iralgin impressions can be immersed or sprayed for disinfection without compromising the accuracy needed for diagnostic and opposing casts, as well as removable partial denture construction.